Best Proximity Point Thorem For Generalized ( - S, Arul Ravi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we establish a new convergence theorem for best proximity of weak contractions in Branciari type generalized metric spaces under weak conditions.